(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
A new genus of "palaeonisciformes", Caelatichthys gen. n., is described on the basis of a well preserved material from the Kalkschieferzone (Meride Limestone) of Ca’ del Frate (Viggiù, Varese) and Meride (Canton Ticino, Switzerland). This small sized fish, with elongate-fusiform body, is characterized by a dermosphenotic in contact with the ventral margin of the dermopterotic, the absence of contact of dermopterotic+dermosphenotic and the nasal bone, the lack of supraorbital bones, the presence of 4-5 infraorbital elements and small premaxilla meeting at the mid-line. Two species were recognized within this genus: C. nitens gen. n., sp. n. and C. meridensis gen. n. sp. n., each exclusive of a single locality. The two species differ in the development of dermal bone ornamentation, in specimens of the same size, and mainly in the pattern of the fulcra of the anal fin. This character cannot be ascribed to sexual dimorphism, as the two fishes showing the two kinds of anal fin were never found together in the same assemblage. The existence of two species of this new genus confirms the great variability of the faunal composition of the different fossiliferous levels of the Kalkschieferzone, with eight species described formally and other whose study is in progress. The good state of preservation of several specimens from Ca’ del Frate also made it possible to reconstruct the growth stages of C. nitens n. gen. n. sp.